The Landscape of CO2 Emissions Across Africa: A Comparative Perspective - (:unkn) unknown (My University, 2022)
Expansion of Global Value Chains (GVCs) is a mixed blessing for the environment. Effects of growth and emissions from transport associated with international trade have negative effects; but greater flows of knowledge and associated spillovers, and adoption of environmentally innovative products have positive effects. This paper provides evidence on carbon dioxide (CO2) emissions for 51 African and 132 other countries for 163 products over the period 1995-2015. The resulting landscape is summarized in four patterns. Patterns identified for the Africa region differ from those identified for other regions but are closely related to a synthetic aggregate comparator constructed on the basis of three characteristics (per capita income, share of manufacturing in GDP, and distance to trading partners).
Keywords: African Research